Pengaruh Laba Kotor, Laba Operasi Dan Laba Bersih Dalam Memprediksi Arus Kas Di Masa Depan (Studi pada Perusahaan Manufaktur yang Listed di BEI Periode 2017-2019) - Ahmad Rully Sri Subchan; Subchan (Jurnal Ekonomi Manajemen Akuntansi, 2021)
The purpose of this study was to examine the effect of gross profit, operating profit and net profit in predicting future cash flows (study of manufacturing companies listed on the IDX for the 2017-2019 period). In this study, the population is the number of manufacturing companies listed on the Indonesia Stock Exchange from 2017-2019, totaling 149 companies. The sample in this research is 19 companies with purposive sampling method. The results of the study show that gross profit has a positive and significant effect on predicting future cash flows with a significance value of 0.000 <0.05, so it can be concluded that gross profit can predict future cash flows in manufacturing companies listed on the IDX for the 2017-2017 period 2019. Operating profit does not have a positive and significant effect on predicting future cash flows with a significance value of 0.774 <0.05, so it can be concluded that operating profit cannot predict future cash flows in manufacturing companies listed on the IDX for the 2017-2019 period. Net profit has a positive and significant effect on predicting future cash flows with a significance value of 0.000 <0.05, so it can be concluded that net income can predict future cash flows in manufacturing companies listed on the IDX for the 2017-2019 period